Cost effectiveness of palm oil in comparison to other oils and fats in the country with special emphasis on lower income group - Singh, R P (Indian Journal of Community Health, 2014)
Fats and oils in the form of vegetable oils are integral part of diet and comprise of an important source of calorie density and micronutrients in human diet. The per capita edible oil consumption in India (14.5 kg in 2012-2013) has been steadily rising over the decades but is still short of the average worldwide consumption in the developed countries. Especially the below poverty line population lags far behind in terms of per capita edible oil consumption and therefore is a major reason for widespread malnutrition. Inadequate consumption of edible oils, which acts as vehicle (mainly promotes absorption in intestine) for important micronutrients like vitamin A, D, E and K, is the root cause behind this. Palm oil is an important source of carotenoids (pro-vitamin A), tocols (Vitamin E), sterols, essential fatty acid and is cost effective in comparison to other edible oils. Crude palm oil which is orange red in color is refined, bleached and deodorized to produce the universally known bright golden oil. Palm oil is a natural semi-solid oil and on fraction it yields soft fraction and hard fraction. Olein (liquid fraction) is mostly used as a cooking and frying oil. Stearin finds many applications in solid fat formulations and is extensively used in food processing.